PROBLEMATIKA PEMBELAJARAN MEMBACA DAN MENULIS PERMULAAN DI SEKOLAH DASAR - Suastika, Nyoman Suastika (Adi Widya: Jurnal Pendidikan Dasar, 2018)
Language is a communication tool that is a symbolic system of sound produced by a human speech tool. Language as a means of communication can not only talk, but can be manifested by hand signals or other bodies that have their own rules. Language has a central role in the intellectual, social, and emotional development of students. This means every human being is subject to limitations in the language. The development of children's speaking skills in elementary schools will become the language for their effective and efficient communication. Learning to read in primary school is very important. This is caused by learning that can not only be utilized in improving the language skills of children, more than that, that is to improve students' ability in learning other subjects. The essence of writing skills is to increase the vocabulary insight for students, so that students are encouraged to think dynamic, critical, rational and able to live up to the conditions and goals of good and true teaching. However, on various matters relating to the process of reading and writing beginning in elementary school. This should not be allowed to happen continuously will cause an imbalance in the development of students' thinking ability. In addition to teachers, parents also play an important role in helping to solve problems by learning to read and write the beginning. Here the authors formulate some efforts to overcome this, namely: choosing reading materials, making the media as a song, choose innovative learning media, and motivate students by providing feedback.